The classification of human and animal bones for forensic osteology aspect - K, Nganvongpanit; T, Pitakarnnop; P, Pakdeenarong (Biomedical Sciences and Clinical Medicine, 2020)
This review article describes the duty of forensic osteology, which is important in the forensic sciences. Forensic osteology is to prove the bones remain that found at the crime scene, humans, or animals? If it is human bone, which sex, age, and cause of death? The screening methods used to identify human and animal bones that will be discussed in this article include; bone anatomy, histological characteristics, and by using the amount of minerals in the bone tissue. The content of this review article will know the concept, application, and limitation of each technique. For the benefit of those interested in the future.